Economic Losses for Rural Land Value Due to Landslides - Zumpano, Veronica; Pisano, Luca; Malek, Žiga; Micu, Mihai; Aucelli, Pietro P. C.; Rosskopf, Carmen M.; Balteanu, Dan; Parise, Mario (Frontiers in Earth Science, 2018)
A high dynamic environment is typically interested by changes affecting the natural processes and their related consequences. Landslides do not only alter the landscape, but substantially affect human activities. When it comes to natural hazards, landslides have been acknowledged as one of the main causes of human casualties or damage to assets. Furthermore, economic losses to rural lands are also significant, despite often being underestimated, especially in rural areas. In territories not densely populated, the main productive activities are in fact often based on the agricultural and pastoral resources. We intend to propose a methodology that helps to investigate the potential loss of value (expressed in EUR) of lands usually exploited for economic profit in rural areas. We test the method on two case studies, belonging to different European Countries with very different economical assets and geological, geomorphological and other environmental conditions. The first study area is situated in the Southern Italian Apennines, in the Molise region, while the second area is located in Buzau County, a region belonging to the Romanian Curvature Carpathians and Subcarpathians Our analysis is focused not only on the actual situation, represented by the past and present landslides, but also on potential future scenarios for 2050. The scenarios foresee future similar socio-economical and technological activities, with no major changes expected. The loss estimation is based on the presence of landslides affecting the rural lands, but it also considers both a present and future landslide susceptibility scenario. This procedure allowed the estimation of the economic losses in the two case-study areas, highlighting how the same natural processes might result in different economic consequences. Following our approach, the results highlight that for the Italian case study there is a loss of 10,45% for 2007 and 9,90% for 2050 of the total land value as concerns landslides susceptibility. In the Romanian case study, on the other hand, the loss corresponds to 29,60% and 29,81% for 2010 and 2050, respectively. In addition, the proposed procedure could be considered a valuable methodological approach to assess landslide-induced economic losses, and be effectively used during spatial planning activities, aimed at supporting decision